Internalization of Pancasila Values in High School Economic Learning in the Digital Era - Munir, Syahrul; Haryono, Agung; Soesilo, Yohanes Hadi; Masruro, Umi (KnE Social Sciences, 2024)
Pancasila is the philosophy of life of the Indonesian people, which has never been swallowed up by the times. Therefore, the values of Pancasila are very important to be internalized by all Indonesian people so that what they do reflects the values of Pancasila. The efforts to internalize the values of Pancasila are through Economics education at the High School (SMA) level. Economic education in high school is reflected in the economic learning activities. This study aims to explain the importance of internalizing Pancasila values in high school economics learning in the digital age. The approach used in this research is a qualitative approach, by conducting a literature study (library research). The results and discussion of this study indicate that in the digital era, it is important to internalize the values of Pancasila in students through economic learning activities, so that they can become a strong fortress and life guide in dealing with any changes that occur in everyday life. The internalization process of Pancasila values is reflected in Economics learning activities, including 1) At the time of teaching, the teacher provides E-Learning guidelines based on Pancasila values in the field of Economics. 2) Teachers instill the values of Pancasila by providing examples of wise management of Economic activities and not destroying nature through visualization with sophisticated technology. 3) Giving group assignments in Economics learning that contains the values of Pancasila. 4) The teacher stimulates students to discuss when solving actual economic issues, both face-to-face and virtual (online). Keywords: internalization, Pancasila, economic learning, digital